Pseudolaguvia virgulata, a new sisorid catfish (Teleostei: Sisoridae) from Mizoram, northeastern India - Ng, Heok Hee; -, Lalramliana (Zootaxa, 2010)
Pseudolaguvia virgulata, a new South Asian sisorid catfish species, is described from the Barak River drainage in Mizoram, India. The new species can be distinguished from congeners in having a brown body with two or three narrow, pale longitudinal stripes and a pale Y-shaped marking on the dorsal surface of the head. Additional distinguishing characters from its congeners are a serrated anterior edge of the dorsal spine, the thoracic adhesive apparatus reaching beyond the base of the last pectoral-fin ray, head width, pectoral-fin length, length of dorsal-fin base, dorsal-spine length, body depth at anus, length of adipose-fin base, caudal peduncle length, caudal peduncle depth, snout length, interorbital distance, and total number of vertebrae.